2003
DOI: 10.1007/s00775-003-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic iron chelators: characterization of the structure, solution chemistry and redox activity of ligands and iron complexes of the di-2-pyridyl ketone isonicotinoyl hydrazone (HPKIH) analogues

Abstract: Di-2-pyridyl ketone isonicotinoyl hydrazone (HPKIH) and a range of its analogues comprise a series of monobasic acids that are capable of binding iron (Fe) as tridentate ( N, N, O) ligands. Recently, we have shown that these chelators are highly cytotoxic, but show selective activity against cancer cells. Particularly interesting was the fact that cytotoxicity of theHPKIH analogues is maintained even after complexation with Fe. To understand the potent anti-tumor activity of these compounds, we have fully char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
173
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(191 citation statements)
references
References 56 publications
15
173
2
1
Order By: Relevance
“…The complexes Fe(PCNH) 2 , Fe(PC4AH) 2 and Fe(PC3AH) 2 each exhibited 4 of the 5 expected peaks from the pyridine carbaldehyde moiety while all other complexes gave only 3 resonances with a large downfield shift. In our previous study with the Fe(PKIH) 2 analogues, 36 we showed that the proton most affected by paramagnetism was that in the 6-position of the coordinated pyridyl ring although in that case the paramagnetism was only very mild by comparison. Extrapolating to this system, we believe that the NMR resonance for the proton attached to atom C1 in Fig.…”
Section: Fe Complexesmentioning
confidence: 80%
See 2 more Smart Citations
“…The complexes Fe(PCNH) 2 , Fe(PC4AH) 2 and Fe(PC3AH) 2 each exhibited 4 of the 5 expected peaks from the pyridine carbaldehyde moiety while all other complexes gave only 3 resonances with a large downfield shift. In our previous study with the Fe(PKIH) 2 analogues, 36 we showed that the proton most affected by paramagnetism was that in the 6-position of the coordinated pyridyl ring although in that case the paramagnetism was only very mild by comparison. Extrapolating to this system, we believe that the NMR resonance for the proton attached to atom C1 in Fig.…”
Section: Fe Complexesmentioning
confidence: 80%
“…This is similar behaviour to that reported in the electrochemistry of the related Fe(PKIH) 2 complexes. 36 Of note, is the significantly more negative potentials exhibited by Fe(PCAH) 2 . This is consistent with the strong electron-donating effect of the 4-aminophenyl substituent disfavouring both metal and ligand based reductions.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, upon PKIH and DpT ligands forming Fe complexes, these ligands generate cytotoxic ROS (10,(26)(27)(28). The resulting oxidative damage potentiates the antiproliferative activity of PKIH and DpT chelators compared with 2-hydroxy-1-naphthylaldehyde isonicotinoyl hydrazone or DFO, which bind Fe but do not redox cycle (29).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting oxidative damage potentiates the antiproliferative activity of PKIH and DpT chelators compared with 2-hydroxy-1-naphthylaldehyde isonicotinoyl hydrazone or DFO, which bind Fe but do not redox cycle (29). The higher activity of DpT series relative to the PKIH class can be ascribed, at least in part, to the electrochemical potentials of their Fe complexes (26,28). In fact, the Fe III/II redox potentials of the Fe(DpT) 2 complexes (ϩ153-225 mV) are much lower than the PKIH analogs (approximately ϩ500 mV) and lie in a range accessible to cellular oxidants and reductants (26,28).…”
Section: Discussionmentioning
confidence: 99%